A spider derived peptide, PnPP-19, induces central antinociception mediated by opioid and cannabinoid systems. Issue 1 (December 2016) - da Fonseca Pacheco, Daniela; Freitas, Ana; Pimenta, Adriano; Duarte, Igor; de Lima, Maria
Abstract Background Some peptides purified from the venom of the spiderPhoneutria nigriventer have been identified as potential sources of drugs for pain treatment. In this study, we characterized the antinociceptive effect of the peptide PnPP-19 on the central nervous system and investigated the possible involvement of opioid and cannabinoid systems in its action mechanism. Methods Nociceptive threshold to thermal stimulation was measured according to the tail-flick test in Swiss mice. All drugs were administered by the intracerebroventricular route. Results PnPP-19 induced central antinociception in mice in the doses of 0.5 and 1 μg. The non-selective opioid receptor antagonist naloxone (2.5 and 5 μg), μ-opioid receptor antagonist clocinnamox (2 and 4 μg), δ-opioid receptor antagonist naltrindole (6 and 12 μg) and CB1 receptor antagonist AM251 (2 and 4 μg) partially inhibited the antinociceptive effect of PnPP-19 (1 μg). Additionally, the anandamide amidase inhibitor MAFP (0.2 μg), the anandamide uptake inhibitor VDM11 (4 μg) and the aminopeptidase inhibitor bestatin (20 μg) significantly enhanced the antinociception induced by a low dose of PnPP-19 (0.5 μg). In contrast, the κ-opioid receptor antagonist nor-binaltorphimine (10 μg and 20 μg) and the CB2 receptor antagonist AM630 (2 and 4 μg) do not appear to be involved in this effect. Conclusions PnPP-19-induced central antinociception involves the activation of CB1 cannabinoid, μ- and δ-opioid receptors. Mobilization of endogenous opioids and cannabinoids might be required for the activation of those receptors, since inhibitors of endogenous substances potentiate the effect of PnPP-19. Our results contribute to elucidating the action of the peptide PnPP-19 in the antinociceptive pathway.